The policy work of piloting: Mobilising and managing conflict and ambiguity in the English NHS. (April 2017) - Bailey, Simon; Checkland, Kath; Hodgson, Damian; McBride, Anne; Elvey, Rebecca; Parkin, Stephen; Rothwell, Katy; Pierides, Dean
Abstract: In spite of their widespread use in policy making in the UK and elsewhere, there is a relatively sparse literature specifically devoted to policy pilots. Recent research on policy piloting has focused on the role of pilots in making policy work in accordance with national agendas. Taking this as a point of departure, the present paper develops the notion of pilots doing policy work. It does this by situating piloting within established theories of policy formulation and implementation, and illustrating using an empirical case. Our case is drawn from a qualitative policy ethnography of a local government pilot programme aiming to extend access to healthcare services. Our case explores the collective entrepreneurship of regional policy makers together with local pilot volunteers. We argue that pilots work to mobilise and manage the ambiguity and conflict associated with particular policy goals, and in their structure and design, shape action towards particular outcomes. We conclude with a discussion of the generative but managed role which piloting affords to local implementers. Highlights: Policy pilots mobilise resources in order to reduce policy ambiguity and conflict. The structure and design of pilots enables and shapes the work of local policy entrepreneurs. Pilots are deemed successful when they shape the emergence of clearer policy objects. The resulting policies become detached from the exceptional conditions of their emergence.